Contraindications for whole body vibration training: a case of nephrolitiasis - Monteleone, G.; de Lorenzo, A.; Sgroi, M.; de Angelis, S.; Di Renzo, L. (The Journal of Sports Medicine and Physical Fitness, 2007)
The use of whole body vibration (WBV) training is becoming more widespread both among athletes and the general public for improving muscle performance. The biological and mechanical effects of WBV are not completely understood and numerous contraindications, that can be identified while obtaining the patient's clinical history, must be taken into consideration. Nephrolithiasis, which often remains asymptomatic for an indefinite time, is not reported in the medical literature as a contraindication to WBV. This paper reports a case of significant morbidity following one session of WBV training in a patient with asymptomatic nephrolithiasis.